Perkembangan Teknologi Beidou Navigation Satellite System (BDS) Tiongkok untuk Melawan Global Positioning System (GPS) Amerika Serikat - Roby Rakhmadi; Cyril Noor Mohammad Harahap (Jurnal Terekam Jejak, 2023)
China successfully launched the third phase of construction in June 2020, making them the third country to independently have their own satellite in orbit after the United States and Russia. The satellite parts, which total 24 satellites, are placed in three different orbits and at the same time make them the owners of the satellites who place the satellites in the three orbits. Beidou has a system that provides higher accuracy and very precise location positioning when compared to GPS navigation satellite systems. The availability of excellent features such as short message service is the main concern in the Beidou feature. Beidou was able to make rapid progress in China's economic and military fields, making it the driving force of China's national security on the mission of becoming a great power country. The comparison is made by placing the GPS satellite system, the world's first navigation satellite which is currently dominantly used in civilian use and military use throughout the world. Beidou's presence led to the view that his presence could counteract the GPS system. With the success of Beidou, creating a new competition between the United States and China in the field of navigation satellites.